(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2009)
Acute appendicitis is one of the common surgical emergencies. Different scoring systems are there in use to diagnose appendicitis. The purpose of this study was to evaluate the diagnostic accuracy of the modified Alvarado scoring system in clinical practice for acute appendicitis. A prospective study was conducted on 100 patients hospitalized with abdominal pain suggestive of acute appendicitis and were subsequently operated, from July 2005 to June 2008 at Bangladesh Rifles (BDR) hospital, Dhaka. Both male and female patients from 7 years to 55 years of age were enrolled in the study. Preoperatively, modified Alvarado score was assigned to all, and the results were compared with operative and histopathological diagnosis. Out of 100 operated patients 84 were diagnosed as a case of acute appendicitis on the basis of histopathological report. Patients with modified Alvarado score of 8-10, 5-7 and 1-4 have the accuracy of 95%, 78%, and 0% respectively. In the higher score group the accuracy is more and acceptable. Lower score group should be kept under observation. Score sensitivity is more in male than female patients. This scoring system is a reliable and practicable diagnostic modality to increase the accuracy in diagnosis of acute appendicitis and thus to minimize unnecessary appendicectomy. Key Words: Alvarado scoring system, Acute appendicitis. doi: 10.3329/jafmc.v5i1.2845 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.18-20